Chitosan nanoparticles as delivery system for nasal immunisation - Janovská, Sylva; Sleha, Radek; Slováková, Marcela; Pudelka, Ludovit; Boštík, Pavel (My University, 2023)
Nasal immunisation represents an innovative and perspective route of vaccine administration that provides many benefits compared to the more traditional approaches. Since most infections start on mucosal membranes, the mucosal immunisation provides a rational reason for its application. Mucosal delivery for vaccine administration (for example oral or nasal routes) could stimulate both systemic and mucosal immune responses. However, there are still some limitations that should be solved for a broader utilisation of this approach. There is still the necessity to use strongly immunogenic antigens or appropriate adjuvants for the induction of a strong immune response. The use of nanoparticles in the vaccine development could represent a promising approach for the mucosal vaccine research. Nanoparticles could thus serve as delivery vehicles providing to vaccines their unique properties, such as the antigen stabilisation and protection, serve as an adjuvant and elicit an antigen-specific immune response on the target sites.
NANOČÁSTICE Z CHITOSANU JAKO DODÁVACÍ SYSTÉM PRO NASÁLNÍ IMUNIZACE
Keywords: Chitosan; nanoparticles; delivery system; nasal; immunisation; Nanočástice; Chitosan; Nasální imunizace